2022
DOI: 10.3390/su141610287
|View full text |Cite
|
Sign up to set email alerts
|

How Is the ESG Reflected in European Financial Stability?

Abstract: Environmental, social, and governance (ESG) factors are increasingly analysed to identify the risks and opportunities in contemporary economies. The banking sector influences the whole economy through the credit channel and balances its stability. The interplay of these elements motivated our main question, whether ESG scores impact European financial stability, measured for the banking sector. To this aim, we employ the cross-quantilogram methodology, which explores dependences at all levels of the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Madison and Schiehll (2021) showed that the individual pillars might have a different sensitivity to materiality issues. Moreover, Lupu et al (2022) found that the impact of the individual pillars on systemic risk varies to a certain degree. Finally, according to the European Banking Authority (2021), especially the E‐Pillar could significantly affect the overall financial system due to the scale and complexity of the environmental risks.…”
Section: Results For Individual E‐ S‐ and G‐pillarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Madison and Schiehll (2021) showed that the individual pillars might have a different sensitivity to materiality issues. Moreover, Lupu et al (2022) found that the impact of the individual pillars on systemic risk varies to a certain degree. Finally, according to the European Banking Authority (2021), especially the E‐Pillar could significantly affect the overall financial system due to the scale and complexity of the environmental risks.…”
Section: Results For Individual E‐ S‐ and G‐pillarsmentioning
confidence: 99%
“…Indeed Scholtens and Van't Klooster (2019) argued that higher sustainability scores could reduce the systemic risk contribution of banks. Similarly, Lupu et al (2022) found evidence that the overall ESG score, as well as the individual pillar score, has a notable impact on the financial stability of banks in Europe, stressing that this influence is nonlinear. Additionally, the duration of ESG disclosure also plays a role, as Chiaramonte et al (2021) showed that it can positively affect stability for European banks.…”
Section: Introductionmentioning
confidence: 95%
“…Based on the examination, the ESG factors had a positive impact on profit as well, therefore it can be considered as an aspect which the banks, the investors and the regulators should also address . Considering the result of the research by Lupu et al (2022), the financial stability of European banks listed on stock exchanges are influenced by their ESG scores (Lupu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…First, risk management is an important pillar of the banking operation. Second, as La Torre et al (2021) and Lupu et al (2022) highlight, regulatory authorities focus on ESG risk and put pressure on banks to understand sustainability risk drivers and translate them into their business models. Following the advocation of Lee and Suh (2022), we examine the association between sustainability and performance through a multi-dimensional approach.…”
Section: Introductionmentioning
confidence: 99%
“…Second, as La Torre et al. (2021) and Lupu et al. (2022) highlight, regulatory authorities focus on ESG risk and put pressure on banks to understand sustainability risk drivers and translate them into their business models.…”
Section: Introductionmentioning
confidence: 99%